Autoethnography: Engaging the Cusp of Praxis and Conjecture - Balogun, Noah Opeyemi; Esoso, Juliana; Ademowo, Adeyemi Johnson (Àgídìgbo: ABUAD Journal of the Humanities, 2020)
Autoethnography is an ethnographic inquiry that utilizes the autobiographic materials of the researcher as the primary data. It is a method as well as a theory which can serve in data analysis as well as useful in situating a research within a paradigm. Although seemingly recent, and has been robustly criticized, the goal of autoethnography, goes beyond merely ‘walking in the shoes’ to ‘engaging the shoe’ and the putting up a narrative for the ‘agent putting on the shoe’. Differing from other self-narrative writings such as autobiography and memoir, autoethnography emphasizes cultural analysis and interpretation of the researcher’s behaviors, thoughts and experiences in relation to others in society. Autoethnography therefore seeks to be ethnographical in its methodological orientation, cultural in its interpretive orientation, and autobiographical in its content orientation. In this work, the authors revisited a review of the nature of this inquiry method, its characteristics and benefits, as well as what it takes to produce a truly scholarly autoethnography without forgetting to unpack some of the observed pitfalls to look out for when doing what we choose to tag ‘good autoethnography’.